Differentiated Learning: A Solution to Increase Students’ Potential Seen from Students’ Readiness to Learn, Interests and Learning Profiles - Kristiawan, Muhamad; Connie, Connie; Asvio, Nova; Risanto, Wisdi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
Differentiated learning is important to be mastered by future teachers, along with the development of education policies in Indonesia that provide equal opportunities for all Indonesian children to learn. This service is in the form of training for prospective teachers which aims to provide them with provisions to be able to teach in classes that have different learning styles, interests, and needs, so that they require different approaches to achieve optimal levels of understanding and achievement. The service method used is a tutorial, where participants are able to use various strategies, such as providing diverse materials, grouping students based on ability or interest, giving different assignments, and providing additional support or challengers according to individual needs. Participants who took part in this service were students of PGMI UIN Fatmawati Sukarno. As a result of the service, the participants have an approach to teaching that allows them to adjust teaching methods, materials, and assessments according to the needs and skill levels of individual students.